(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Water was among the most extensively used chemicals on our world. All of our everyday activities need the use of water. In most urban locations, water supply is frequently in short supply relative to demand. Because surface water is inadequate to meet our requirements, we must depend on underground water. As a consequence of expanding urbanization, rainwater penetrating into the groundwater has dropped substantially, and groundwater flow has diminished. In this instance, an alternative source is important to balance the demand-supply imbalance. Rainwater, the purest sort of water, would be an immediate source to replace the present water supply by "gathering water wherever it falls." Rainwater harvesting is the practice of collecting and storing rainwater in a systematic and controlled manner for future use.In this paper we discussed about the advantages and disadvantages of rain water harvesting with different technique. The future scope of this study is to understanding the whole scenario of water harvesting.